Research priorities on computerization in Mlaysia with special reference to governmental systems. - Han , Chun Kwong; Mohamed, Mohd Zain (1986)
Beginning with an analysis of the 20 year history and current trend of computerization in Malaysia, this paper maps out prioritized areas of research in order to understand its contribution and impacts to development and society. The high priority research are in the area of macro policy issues; profit and productivity impacts; microcomputer utilization in business, education and government verylarge database; computer industry economics; computer education; industrial sector analysis; and human aspects of computerization. The overall research mission is to develop a success model of computerization, at both macro and micro levels. Of particular relevance to governmental systems is an organizational activity model of government departments which will facilitate asseaament of the impact of information technologies on decision making. The interdisciplinary approach in an environment of mutual understanding and mutual adjustment is advocated as the mechanism for implementing these studies of the behavioral, cultural, economic, social and technological aspects and implications of the information revolution in Malaysia.